The Role of Micro, Small, and Medium Enterprises (MSMEs) in Driving the Local Economy: An Empirical Study in Rural Areas - Meida Rachmawati (Edusight International Journal of Multidisciplinary Studies, 2026)
This study analyzes the role of Micro, Small and Medium Enterprises (MSMEs) in driving local economy in rural areas of Indonesia. Using quantitative approach with primary data from 250 MSMEs in five districts in Central Java during 2022-2024 period, this research shows that MSMEs provide significant contribution to rural community income increase by 34.7% and job creation reaching 2,847 people. Regression analysis results indicate that access to capital, technology, and training are main factors affecting MSME performance with R² value of 0.743. Processed agriculture and handicraft sectors show highest growth with average of 28.5% annually. The study finds that MSMEs can increase local community purchasing power up to 42.3% and reduce population migration to cities by 18.9%. These findings indicate that MSMEs have strategic role in driving rural economic wheels through creating added value of local products and community empowerment.